Analysis of The Implementation of Differentation Learning in Class V Primary Schools Based on The Independent Curriculum - Fitriyah, Laila Khanifatul; Gunarhadi, Gunarhadi; Suryandari, Kartika Chrysti (Social, Humanities, and Educational Studies (SHES): Conference Series, 2024)
This research is descriptive qualitative research using observation, interview and documentation study methods which aims to analyze the implementation of differentiated learning in class V elementary school based on the independent curriculum at SDN Jimbaran 01 Bandungan. The research subjects were the principal and class V teacher at SDN Jimbaran 01. The research results showed that 1) teachers had difficulty carrying out initial diagnostic assessments, especially for quiet children. 2) teachers have difficulty integrating differentiated strategies into learning steps in preparing teaching modules. 3) There is a slight misperception that differentiated learning is creating a learning design that is similar to individual mentoring. Based on the results of the analysis of observations and interviews with teachers, it can be concluded that in analyzing differentiation there are still some difficulties, especially in implementing differentiated learning in the classroom. So there is a need for further training for teachers who have implemented the independent curriculum in the learning process in their classes, especially class V.